2018
DOI: 10.1038/s41598-018-25633-z
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of demographic decline across the annual cycle of a threatened migratory bird

Abstract: Migratory species are rapidly declining but we rarely know which periods of the annual cycle are limiting for most species. This knowledge is needed to effectively allocate conservation resources to the periods of the annual cycle that best promote species recovery. We examined demographic trends and response to human footprint for Canada warblers (Cardellina canadensis), a threatened Neotropical migrant, using range-wide data (1993–2016) from the Monitoring Avian Productivity and Survivorship (MAPS) program o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 53 publications
1
73
0
Order By: Relevance
“…Furthermore, both of these solutions require modification to account for transiency, which is not straightforward in the context of JS or reverse‐symmetry models. Despite having little direct information on recruitment in our model and imprecise estimates of the first‐year survival/immigration component of recruitment (ι), our results implicating the importance of recruitment in explaining temporal variation in population growth rates are consistent with results of analyses based on MAPS data alone for a variety of bird species, including Wilson's warbler (DeSante et al, ; Wilson et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, both of these solutions require modification to account for transiency, which is not straightforward in the context of JS or reverse‐symmetry models. Despite having little direct information on recruitment in our model and imprecise estimates of the first‐year survival/immigration component of recruitment (ι), our results implicating the importance of recruitment in explaining temporal variation in population growth rates are consistent with results of analyses based on MAPS data alone for a variety of bird species, including Wilson's warbler (DeSante et al, ; Wilson et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Many studies have indicated that accounting for environmental conditions on the wintering grounds and during migratory periods is important for understanding population dynamics of migratory birds (e.g., Balbontin et al, ; Drake, Rock, Quinlan, Martin, & Green, ; Sheehy, Taylor, & Norris, ). For example, an analysis of long‐term monitoring data for the Canada Warbler ( Cardellina canadensis ) indicated that declining trends were associated with reduced survival during the nonbreeding period (Wilson et al, ), and analyses of long‐term monitoring data for the American Redstart ( Setophaga ruticilla ) showed that temporal variation in wintering grounds habitat quality was a strong predictor of changes in abundance on the breeding grounds (Wilson, LaDeau, Tottrup, & Marra, ). Kirtland's Warbler is one of the few species with quantitative empirical models that link environmental conditions on the wintering grounds to population vital rates (Rockwell et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent population declines over the last 50 years in species that overwinter primarily in montane habitats in the Northern Andes of South America are associated with habitat loss and deterioration on the wintering grounds (Jones et al 2004, González-Prieto et al 2017, Kramer et al 2018, Wilson et al 2018. For instance, species of conservation concern such as the Cerulean Warbler (Setophaga cerulea), Canada Warbler (Cardellina canadensis), and Olivesided Flycatcher (Contopus cooperi) have a predominantly Andean wintering distribution and have experienced steep declines in their populations in recent decades (Sauer et al 2017) (Fig.…”
mentioning
confidence: 99%
“…For instance, more than 60% of the Canada Warbler population has been lost over the last four decades (Sauer et al 2017), more than 50% of its winter range is located within the Andes of Colombia, and land use changes in Andean winter grounds are likely the primary source of population decline (Wilson et al 2018). In the face of this worrying situation, we can choose to be part of the solution for winter habitat loss for Neotropical migrants by informing other citizens and making ethical coffee choices.…”
mentioning
confidence: 99%